STRATEGI PEMASARAN SYARIAH JAHE MERAH KELOMPOK TANI DI DESA SUNGAI MULUK - Ari Gintara Putra; Putri Apria Ningsih; M Taufik Ridho (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to find out Sharia marketing strategies and the inhibiting and supporting factors of the Sungai Muluk Village farmer group, this research is qualitative type using primary and secondary data sources. The object of this research is a number of members or red ginger farmers from Sungai Muluk village. Data was obtained directly from 15 respondents using data analysis methods, namely observation, interviews and personal documentation, then the data was processed using data processing techniques and SWOT analysis. The results of the research show that: The red ginger farmer group in Sungai Muluk village, in implementing their marketing strategy, uses the characteristics recommended or guided by the Prophet Muhammad SAW, namely Theistic, Ethical, Realistic and Humanist, the marketing strategy implemented by the red ginger farmer group Sungai Muluk village is not running smoothly because there are several inhibiting factors, namely, insufficient capital, competition and price and supporting factors, namely product and location.